Deformation Control of Subway Tunnels Undercrossing Airport Facilities: A Case Study of the Xinzheng Airport Rail Transit Hub Project - Zhang Liqiang; Jinxing Zhao; Qi Le (Advances in Civil Engineering)
The rapid expansion of urban areas due to China’s booming economy has led to a conflict between people and vehicular traffic. Consequently, rail transit, represented by subways, has become the primary mode of transportation for residents. However, the influence of soil damage on tunnel deformation is often overlooked in research on the safety of soft soil tunneling, leading to discrepancies between the results predicted by models and the actual settlement of tunnels. In this study, soil investigation and mechanical strength testing were carried out to analyze the impact of aircraft takeoff and landing activities on the Xinzheng Airport facilities. Damage variables are introduced into the Drucker‒Prager ideal elastic‒plastic criterion, and a soft soil tunneling model with soil deformation is established to investigate the spatial and temporal effects of the shield-cutting force, moving aircraft load, and tunnel deformation. Based on the synchronous grouting technique, a mechanical load-bearing system consisting of a concrete runway, solidified grout, and high-strength segments is formed to ensure the safety of flight activities.